BREAKING THE CIRCULATION OF HATE, IMPRISONING THE TERRORISTS: THE CONTAINMENT EFFORT FOR THE SPREAD OF ISIS RADICALISM IN INDONESIA - Helmi Zaky Mardiansyah (UIN Kiai Haji Achmad Siddiq Jember, 2023)
The Islamic State in Iraq and Syria (ISIS) spreads radical terror and invites people to commit violence to achieve their goals. ISIS also spreads hatred towards other groups contrary to their views based on their exclusive religious understanding. They consider their group to be the most righteous and others to be apostates or infidels, including the state or the government. Therefore, the Indonesian government must be wary of this group. Thus, the Indonesian government has banned ISIS radicalism in Indonesia because it is not by the values of Pancasila and the constitution. This research examines the imprisoning policy of the perpetrators of spreading ISIS radicalism and the form of policy formulation as a containment effort for terrorism crimes in the future. This normative juridical research method uses a statute approach and a conceptual approach. This research shows that the policy is that criminal responsibility for spreading radicalism can be imposed on individuals and groups, whether civilian, military, or police, who are responsible individually, or corporations. The corporation in question is an institution that is suspected and proven to have spread radicalism which leads to acts of terrorism. This crime originates from the regeneration of terrorist cells, which develop despite the different ways and modes of carrying out their actions. In addition, different perspectives on ideology also encourage the proliferation of terrorist cells that seek to incorporate Islamic law constitutionally and change Pancasila with an exclusive religious ideology.